Functionalized graphene oxide in microbial engineering: An effective stimulator for bacterial growth. (July 2016) - Luo, Yinchan; Yang, Xinxing; Tan, Xiaofang; Xu, Ligeng; Liu, Zhuang; Xiao, Jie; Peng, Rui
Abstract: Whether graphene and graphene oxide (GO) would affect the activities of bacteria has been under debate. Nevertheless, how graphene derivatives with biocompatible coatings interact with microorganisms and the underlying mechanisms are important issues for nanobiotechnology, and remain to be further explored. Herein, three new types of nano-GOs functionalized with polyethylene glycol (nGO-PEGs) were synthesized by varying the PEGylation degree, and their effects on Escherichia coli ( E. coli ) were carefully investigated. Interestingly, nGO-PEG (1:1), the one with relatively lower PEGylation degree, could significantly stimulate bacterial growth, whereas as-made GO and the other two nGO-PEGs showed no effect. Further analysis revealed that nGO-PEG (1:1) treatment significantly accelerated FtsZ-ring assembly, shortening Phase 1 in the bacterial cell cycle. Both DNA synthesis and extracellular polymeric substance (EPS) secretion were also dramatically increased. This unique phenomenon suggests promising potentials in microbial engineering as well as in clinical detection of bacterial pathogens. As a proof-of-concept, nGO-PEG (1:1) treatment could remarkably enhance (up to 6-fold) recombinant protein production in engineered bacteria cells. To our best knowledge, this is the first demonstration of functionalized GO as a novel, positive regulator in microbial engineering. Moreover, our work highlights the critical role of surface chemistry in modulating the interactions between nanomaterials and microorganisms.